A Masked Phosphinidene Trapped in a Fluxional NCN Pincer. Issue 49 (24th October 2016) - Hyvl, Jakub; Yoshida, Wesley Y.; Rheingold, Arnold L.; Hughes, Russell P.; Cain, Matthew F.
Abstract: The trapping of a phosphinidene (R‐P) in an NCN pincer is presented. Stabilized phosphinidene1 was characterized by 31 P 1 H, 1 H, and 13 C 1 H NMR spectroscopy, exhibiting an averaged C 2 v symmetry in solution between −60 and 60 °C. In the solid state, the phosphinidene is coordinated by one adjacent N atom featuring a formal P−N bond (1.757(2) Å) to give a five‐membered ring with some aromatic character, confirmed by DFT calculations (B3LYP‐D3/6‐311G**++) to be the ground‐state structure. Equilibration of the two N ligands occurs rapidly in solution via a "bell‐clapper"‐type process through an associative symmetric transition state calculated to lie 4.0 kcal mol −1 above the ground state. Abstract : The bell tolls for P : The trapping of a phosphinidene (R−P) in an NCN pincer is presented. In the solid state, the phosphinidene is coordinated by one adjacent N atom featuring to give a five‐membered ring with some aromatic character. Equilibration of the two N ligands occurs rapidly in solution via a "bell‐clapper"‐type process.